Transient establishment of imprinted DNA methylation of transgenic human IC1 sequence in mouse during the preimplantation period. (1st December 2020) - Hirakawa, Katsuhiko; Matsuzaki, Hitomi; Tanimoto, Keiji
Abstract: Monoallelic gene expression at the Igf 2/ H19 locus is controlled by paternal allele-specific DNA methylation of the imprinting control region ( H19 ICR) that is established during spermatogenesis. We demonstrated that the H19 ICR fragment in transgenic mice acquires allele-specific methylation only after fertilization, which is essential for maintaining its allelic methylation during early embryogenesis. We identified a DNA element required for establishing postfertilization methylation within a 118 bp (m118) region. A previously generated knock-in mouse whose endogenous H19 ICR was substituted with the human H19 ICR (hIC1; 4.8 kb) sequence revealed that the hIC1 sequence was partially methylated in sperm, although this methylation was lost by the blastocyst stage, which we assume is due to a lack of an m118-equivalent sequence in the hIC1 transgene. To identify a cis sequence involved in postfertilization methylation within the hIC1 region, we generated three transgenic mouse lines (TgM): one carrying an 8.8 kb hIC1 sequence joined to m118 (hIC1+m118), one with the 8.8 kb hIC1 and one with the 5.8 kb hIC1 sequence joined to m118 (hIC1–3′+m118). We found that the hIC1–3′ region was resistant to de novo DNA methylation throughout development. In contrast, the 5′ portion of the hIC1 (hIC1–5′) in both hIC1+m118 and hIC1 TgM were preferentially methylated on the paternal allele only during preimplantation. As DNA methylation levels were higher in hIC1+m118, the m118 sequence could also induce imprinted methylation of the human sequence. Most importantly, the hIC1–5′ sequence appears to possess an activity equivalent to that of m118.